Painful thumb carpometacarpal joint osteoarthritis: Results of a novel treatment approach. Issue 7 (July 2016) - Ehrl, Denis; Erne, Holger C.; Broer, P. Niclas; Metz, Christian; Falter, Erwin
Summary: Background: Pain reduction as well as preservation and improvement in range of motion remain the main aims in the treatment of thumb carpometacarpal (CMC) osteoarthritis (OA). We performed a retrospective outcome analysis of patients with symptomatic stage II–III thumb CMC joint arthritis treated with denervation, joint lavage and capsular imbrication. Methods: 73 patients with stage II to III OA of the thumb CMC-joint underwent the described technique. A total of 42 patients complied with follow-up assessment and were included in this study. Mean follow-up was 41.2 (range 12–81) months. Results: Mean operative time was 28.4 (±6.5) minutes. The follow-up assessments showed a significant decrease in pain (preoperative Numerical Rating Scale (NRS): 7.5 – postoperative NRS: 1.1) (p < 0.0001) and a significant improvement in function of the thumb (preoperative DASH-Score: 46.8; Cooney-Wrist-Score: 35.4; Krimmer-Wrist-Score: 38.3 – postoperative DASH-Score: 18.1; Cooney-Wrist-Score: 73.7; Krimmer-Wrist-Score: 80.0) (p < 0.0001). Conclusion: The findings of our study indicate that the presented treatment approach could be a good alternative to more invasive surgical options in patients with stage II–III CMC OA of the thumb, without impairing more invasive surgical options like trapeziectomy or arthroplasty for the future.